2022
DOI: 10.4012/dmj.2022-018
|View full text |Cite
|
Sign up to set email alerts
|

CAD/CAM lithium disilicate ceramic crowns: Effect of occlusal thickness on fracture resistance and fractographic analysis

Abstract: This study uses fracture tests and fractographical analysis to compare computer-aided design and computer-aided manufacturing (CAD/CAM) lithium disilicate molar crowns with the previous occlusal thickness recommendation of 1.5-mm, the new recommendation of 1.0-mm, and a less invasive thickness of 0.8-mm. After fatigue application, fracture tests and fractographic analysis were conducted. The fracture resistance of CAD/CAM lithium disilicate molar crowns was different depending on the occlusal thickness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…23 Monolithic CAD/CAM fabricated LDS molar crowns were also tested in different ceramic layer thicknesses (0.5-1.5 mm) and various fatigue protocols. 28,34,39,47 Lower and partly unsatisfactory failure load values of 470 N (without fatigue) and 369 N (with fatigue) for 0.5 mm, 801 N (without fatigue) and 889 N (with fatigue) for 1.0 mm, 1107 N (without fatigue) and 980 N (with fatigue) for 1.5 mm LDS molar crowns were observed with a similar aging protocol (1.2 million cycles, 108 N). 47 Yet, the study loaded the specimens in a 30 angle, perpendicular to one cusp and with a higher load during fatigue (108 N) which might explain the lower fracture values.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…23 Monolithic CAD/CAM fabricated LDS molar crowns were also tested in different ceramic layer thicknesses (0.5-1.5 mm) and various fatigue protocols. 28,34,39,47 Lower and partly unsatisfactory failure load values of 470 N (without fatigue) and 369 N (with fatigue) for 0.5 mm, 801 N (without fatigue) and 889 N (with fatigue) for 1.0 mm, 1107 N (without fatigue) and 980 N (with fatigue) for 1.5 mm LDS molar crowns were observed with a similar aging protocol (1.2 million cycles, 108 N). 47 Yet, the study loaded the specimens in a 30 angle, perpendicular to one cusp and with a higher load during fatigue (108 N) which might explain the lower fracture values.…”
Section: Discussionmentioning
confidence: 61%
“…39 A study with a prolonged fatigue application (5 million cycles, 275 N) lead to slightly lower failure load values of 980 N (0.8 mm), 1162 N (1.0 mm) and 1540 N (1.5 mm) compared to the obtained results of the present study. 28 Ceramic bulk fractures are still the most common complication for onlays, PCRs, and crowns in clinical observations. 40,41 Failure modes after SLF revealed more bulk fractures with involvement of the fractures without involvement of the tooth for thin restorations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chairside CAD‐CAM lithium disilicate crowns for anterior and posterior teeth have become a widespread option for clinical dentistry 31,32 . In fact, a recent practice‐based study indicated that this ceramic was the second most commonly used material for single restorations 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Chairside CAD-CAM lithium disilicate crowns for anterior and posterior teeth have become a widespread option for clinical dentistry. 31,32 In fact, a recent practice-based study indicated that this ceramic was the second most commonly used material for single restorations. 10 The purpose of this study was to determine whether crowns without and with different endodontic accesses display different fracture resistance.…”
Section: Discussionmentioning
confidence: 99%